Husband and wife with sarcoidosis: possible environmental factors involved - Leli, Ilaria; Salimbene, Ivano; Varone, Francesco; Fuso, Leonello; Valente, Salvatore (Multidisciplinary Respiratory Medicine, 2013)
Sarcoidosis is a granulomatous multisystem disorder of unclear etiology that involves any organ, most commonly the lung and the lymph nodes. It is hypothesized that the disease derives from the interaction between single or multiple environmental factors and genetically determined host factors. Multiple potential etiologic agents for sarcoidosis have been proposed without any definitive demonstration of causality. We report the case of two patients, husband (57 years old) and wife (55 years old), both suffering from sarcoidosis. They underwent a lymph node biopsy by mediastinoscopy which showed a “granulomatous epithelioid giant cell non-necrotising chronic lymphadenitis”. They had lived up to 3 years ago in the country in a farm, in contact with organic dusts, animals such as dogs, chickens, rabbits, pigeons; now they have lived since about 3 years in an urban area where there are numerous chemical industries and stone quarries. The aim of this case report was to focus on environmental factors that might be related to the pathogenesis of the sarcoidosis.